A transcriptional silencer controls the developmental expression of the CD4 gene. - Siu, G (1994)
The appropriate expression of the CD4 glycoprotein is required for T-cell function and development. Here we define the transcriptional control elements in the CD4 locus that convey CD(4+)-specific expression of a marker gene in transgenic mice. Using nuclear run-on experiments, we have determined that the major mechanism for CD4 expression control during development is transcriptional. We have identified a developmental stage- and tissue-specific negative regulatory element in the first intron of the murine CD4 gene that has the characteristics of a transcriptional silencer. The CD4 silencer functions to inhibit marker gene expression at two different stages of T-cell development, as well as in non-T hematopoietic cells, and thus is the critical controlling element responsible for T-cell-specific, as well as developmental- and subclass-specific, expression.